Brain iron accumulation in Wilson disease: a post mortem 7 Tesla MRI - histopathological study - Dusek, P; Bahn, E; Litwin, T; Jabłonka-Salach, K; Łuciuk, A; Huelnhagen, T; Madai, V I; Dieringer, M A; Bulska, E; Knauth, M; Niendorf, T; Sobesky, J; et al. (Neuropathology and applied neurobiology, 2017)
AIMS: In Wilson disease (WD), T2/T2*-weighted (T2*w) MRI frequently shows hypointensity in the basal ganglia that is suggestive of paramagnetic deposits. It is currently unknown whether this hypointensity is related to copper or iron deposition. We examined the neuropathological correlates of this MRI pattern, particularly in relation to iron and copper concentrations. METHODS: Brain slices from nine WD and six control cases were investigated using a 7T-MRI system. High-resolution T2*w images were acquired and R2* parametric maps were reconstructed using a multigradient recalled echo sequence. R2* was measured in the globus pallidus (GP) and the putamen. Corresponding histopathological sections containing the lentiform nucleus were examined using Turnbull iron staining, and double staining combining Turnbull with immunohistochemistry for macrophages or astrocytes. Quantitative densitometry of the iron staining as well as copper and iron concentrations were measured in the GP and putamen and correlated with R2* values. RESULTS: T2*w hypointensity in the GP and/or putamen was apparent in WD cases and R2* values correlated with quantitative densitometry of iron staining. In WD, iron and copper concentrations were increased in the putamen compared to controls. R2* was correlated with the iron concentration in the GP and putamen, whereas no correlation was observed for the copper concentration. Patients with more pronounced pathological severity in the putamen displayed increased iron concentration, which correlated with an elevated number of iron-containing macrophages. CONCLUSIONS: T2/T2*w hypointensity observed in vivo in the basal ganglia of WD patients is related to iron rather than copper deposits.
Keywords: železo; iron accumulation; Magnetic Resonance Imaging; pathology; post mortem 7T MRI; magnetická rezonanční tomografie; Corpus Striatum; Humans; Iron; lidé středního věku; Copper; Hepatolenticular Degeneration; Female; makrofágy; dospělí; mladý dospělý; lidé; corpus striatum; brain; měď; Adult; bazální ganglia; ženské pohlaví; Male; Astrocytes; Middle Aged; Wilson disease; Young Adult; Basal Ganglia; Macrophages; astrocyty; mužské pohlaví; hepatolentikulární degenerace